NON-STATE SPECIAL OPERATIONS capabilities and effects. - RICE, IAN (ROUTLEDGE, 2026)
This book examines how violent non-state actors (VNSAs) emulate and develop military special operation capabilities.Building on previous research on Islamic State special operations, the book develops a theoretical framework surrounding a typology of VNSA (militants, proxies, criminal/cults, and mercenaries) to explore variations of non-state special operations, with multiple cases for each category of actor. Understanding when and why VNSAs use special operations provides insights into the inner workings of such groups and how they campaign and also has implications for the proliferation of special operation forces around the globe and its influence on non-state behavior. This volume contributes to research on the recent trend of non-state actors surprising, and in some cases humiliating, their state opponents.This book will be of much interest to students of military and strategic studies, defense studies, and security studies.